Electron transfer behavior of monolayer protected nanoclusters and nanowires of silver and gold - Sharma, Jadab; Vivek, J. P.; Vijayamohanan, Kunjukrishna P. (Journal of Nanoscience and Nanotechnology, 2006)
Understanding the electron transfer behavior of nanometer sized, both metallic and semiconducting particles and wires is important due to the fundamental interest in size and shape dependent electronic properties and also because of its applications in nano-electronic devices like single electron transistors and molecular switches. Monolayer protected nanoclusters enable one simple and elegant method of synthesis of these types of metallic and semiconducting materials using interfacial chemistry as has been successfully used in several applications ranging from catalysis to molecular electronics. The success of this type of nanostructured materials is due in part to the well known protecting/stabilizing action of the ligands (also known as surface passivating/capping agents), which facilitate the synthesis and processing of these hydrophobic colloids in solution form. The present article discusses the electron transfer behavior of silver nanowires and nanoparticles with varied sizes. In particular, we have investigated the electrochemical properties of silver nanowires (diameter 70 nm, length several micrometers) and compared with the behavior of similar relatively larger sized nanoparticles (size 40 nm). A critical analysis of the redox behavior of silver nanowires and nanoparticles is presented in aqueous medium under various electrolytic conditions along with a comparison of analogous properties of smaller sized (2-7 nm) silver and gold nanoclusters.
Keywords: cyclic voltammetry; nanoclusters/nanoparticles; Nanowires